Desarrollo de un recorrido virtual interactivo para el Campus Matriz de la Universidad Técnica de Cotopaxi aplicando la metodología lean - Maldonado Campaña, Patricia Priscila (2022)
This degree project consists on a 360º interactive virtual tour development of Technical University of Cotopaxi campus which is aimed to all user who want to interact with the application. For its development, it has been necessary to research about concepts and techniques that are related to virtual tours development. LEAN methodology was used which helps to eliminate waste from the project, and the .net programming language was developed with Panellum.js library. To select strategic places of University the structural organization chart proposed by the institution was taken as a reference, and in turn observation technique that allowed to choose and gather information about different places of the main campus institution, as well as 360º images, photographs, edition and finally the creation of interactive virtual tour. It is considered that it is a project that will benefit Technical University of Cotopaxi due to the fact that through the tour greater interest will be encouraged among users to know its facilities such as: laboratories, classrooms, libraries, auditoriums, administrative areas, to visit it physically. That is why virtual tour generates a technological plus for the university through 360° photography technique that is being used today by large companies at a national and international level to guide, show projects, as well as in educational, cultural and technological fields.